Dwarf walls of the Mandapa of the Mahanaleshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The corners of the dwarf walls of the mandapa (pillared hall) of the Mahanaleshwar Temple have icons at their joining juncture. These images are mostly of dikapalas (gods of cardinal directions), the directional deities, but since the icons are mutilated, it is difficult to identify them. The west-facing devakoshtha (niche) seen here probably had the icon of Ishan, the god of the north-east direction. The base of the dwarf walls with devakoshthas (niches) have two sets of pillars at their edges. One of these is a half pillar that rests over the kakshasana (seat backs) from the interiors of the temple and the other is a pilaster that connects to the perforated windows of the mandapas.